Climate Change and Building Energy Consumption: A Review of the Impact of Weather Parameters Influenced by Climate Change on Household Heating and Cooling Demands of Buildings - Bazazzadeh, Hassan; Nadolny, Adam; Safaei, Seyedeh Sara Hashemi (European Journal of Sustainable Development, 2021)
The growth of urban population as the result of economic and industrial development has changed our place of living from a prosperous place to where the resources are carelessly consumed. On the other hand, long-term climate change, i.e. global warming, has had adverse impact on our resources. Certain resources are on the verge of depletion as the consequence of climate change and inconsiderate consumption of resources, unless serious measures are implemented immediately. The building sector, whose share in the municipal energy consumption is considerably high, is a key player that may successfully solve the problem. This paper aims to study the effects of climate change on the energy consumption of buildings and analyze its magnitude to increase the awareness of how construction can reduce the overall global energy consumption. A descriptive-analytical method has been applied to analyze valid models of energy consumption according to different scenarios and to interpret the conditions underlying current and future energy consumption of buildings. The results clearly show that the energy consumption in the building sector increasingly depends on the cooling demand. With that being said, we can expect the reduction of overall energy consumption of buildings in regions with high heating demands, whereas rising the energy consumption in buildings is expected in regions with high cooling demand. To conclude, the long-term climate change (e.g. global warming) underlies the increased energy consumption for the cooling demand whose share in total energy consumption of buildings much outweighs the heating demand. Therefore, to conserve our resources, urban energy planning and management should focus on working up a proper framework of guidelines on how to mitigate the cooling loads in the energy consumption patterns of buildings.